40 Centuries of State and Legal Thought (review for the first Part of the textbook by O. M. Holovko and T. Ye. Kahanovska "History of the Doctrines on Law and State") (Law and Safety, 2020)
The authors set themselves an important task in terms of volume and depth: to reveal the value of the thoughts of their great predecessors and to bring these treasures to the minds of students of the XXI century. I am convinced that they succeeded in full. The language of the textbook, its imagery and liveliness, the success of quotations, the original author's commentary, the depth of conclusions - all these are the characteristic features of the peer-reviewed work. It has many advantages and benefits, and it is difficult to say everything in a fairly short review, but we will say one more thing. Undoubtedly, this book will help improve the training of the new generation of lawyers, give them a basis for reflection on some of the eternal problems of jurisprudence - theoretical and practical, closely related to their present and future lives. reference book on this historical and legal discipline.